GLOBAL COMMUNICATION ETHICS AND DIGITAL LITERACY: BUILDING A MODERATE VIRTUAL LEARNING SPACE IN THE CYBER ERA - Soni Ariawan; Jumarim; Akhmad Asyari; Suparlan (Tahiro : Journal of Peace and Religious Mederation, 2026)
This research examines the convergence of global communication ethics and digital literacy within the context of English Language Teaching (ELT) in the cyber era, grounded in the values of Islamic moderation (Islam Washathiyah). The study takes the form of an analytical-critical literature review reinforced by global empirical data on the contemporary digital landscape. The main conceptual contribution of this research lies in the repositioning of Washathiyah: not merely as a complementary value or ethical qualifier to existing Western frameworks of digital literacy and intercultural competence, but as an epistemological principle that reshapes how those frameworks are understood and operationalized. By integrating the Spectrum Concept of the Self theory, the framework of intercultural communicative competence, and critical digital literacy models, this research argues that the greatest threats within the digital ecosystem ranging from disinformation and hate speech to online radicalization are manifestations of a systemic ethical crisis. Data show that Indonesia, with 212 million active internet users and a digital literacy ranking of 64th out of 100 countries, stands at a critical crossroads between digital opportunity and threat. The findings identify three Washathiyah-based protective mechanisms that are genuinely novel in their framing: (1) critical digital literacy as an epistemological shield against disinformation, rooted in the principle of tabayyun rather than merely borrowed from it; (2) intercultural communicative competence grounded in the values of ta'aruf and tasamuh, which reconstructs not merely supplements Byram's ICC model; and (3) the design of a moderate virtual learning space (the WASH Framework), which positions teachers as facilitators of digital ethics. The implications of this research extend beyond the ELT context and offer a framework for the entire Muslim educational ecosystem in the cyber era.